Pope Productions Chiasma - Pope Productions (Pope Productions, 2003)
Poster for the Chiasma live streams at Pope Productions in St. John's, Newfoundland. Collected material from Chiasma by Léa Donnan, Rebecca Belmore, and Hester Reeve.